Activation of Ah receptor by pure humic acids - Bittner, Michal; Janosek, Jaroslav; Hilscherová, Klára; Giesy, John; Holoubek, Ivan; Bláha, Ludĕk (Environmental toxicology, 2006)
Humic substances (HS) are ubiquitous in the environment. However, some studies indicate that HS could induce direct adverse effects on human health and hormone-like effects in fish, amphibians, and invertebrates. In this study we investigated a possible biochemical mechanism of HS toxicity via activation of the aryl hydrocarbon receptor (AhR). AhR mediates the toxic and biological effects of environmental contaminants such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), but a number of structurally diverse compounds has also been found to activate AhR. Alkali solutions of humic acids (HA) were prepared, and subsequently, lipophilic compounds (including parts of HA) were extracted by liquid-liquid extraction with hexane/dichloromethane. Organic extract of HA was further treated with sulfuric acid to study the role of possible trace persistent contaminants. In vitro dioxin-like activities of obtained extract and HA solutions have been evaluated using H4IIE.luc cells by determining the ethoxyresorufin-O-deethylase (EROD) activity and induction of AhR-dependent reporter luciferase. Traces of nonpersistent residues in HA with known AhR activity were identified and quantified by GC-MS. Our results show that an alkali solution as well as organic extract of HA were active in both EROD and luciferase assays, while H2SO4-treated extract activity was negligible. Only nonsignificant levels of AhR-inducing contaminants (PAHs and PCBs) were found in the HA samples. Our results indicate that HA or their fragments can elicit significant inductions of AhR-mediated effects in vitro. To our best knowledge, this study is the first in providing direct evidence of dioxin-like effects of HA. Further efforts should focus on detailed characterization of potential toxic effects of various HSs.
Keywords: Humic Substances; Genes, Reporter; huminové látky; Rats; nádorové buněčné linie; Receptors, Aryl Hydrocarbon; cytochrom P-450 CYP1A1; reportérové geny; krysa rodu Rattus; Cell Line, Tumor; luciferasy; Animals; Luciferases; zvířata; receptory aromatických uhlovodíků; Cytochrome P-450 CYP1A1